The complete mitogenome of the Australian spiny crayfish Euastacus yarraensis (McCoy, 1888) (Crustacea: Decapoda: Parastacidae). (3rd March 2016) - Gan, Han Ming; Tan, Mun Hua; Austin, Christopher M.
Abstract: The mitochondrial genome sequence of the Australian crayfish, Euastacus yarraensis, is documented and compared with other Australian crayfish genera. Euastacus yarraensis has a mitogenome of 15, 548 base pairs consisting of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a non-coding AT-rich region. The base composition of E. yarraensis mitogenome is 32.39% for T, 22.45% for C, 34.43% for A, and 10.73% for G, with an AT bias of 66.82%. The mitogenome gene order conforms to what is considered the primitive arrangement for parastacid crayfish.